소아 천식 환아에서 호기 온도 측정의 임상적 의의 - 김수연; 김정윤; 한윤기; 김종덕; 설인숙; 박영아; 김윤희; 김경원; 손명현; 김규언 (Allergy asthma & respiratory disease, 2017)
Purpose: Exhaled breath temperature (EBT) has been suggested as a noninvasive marker of airway inflammation in asthma. The aim of this study was to determine its clinical implication in children with asthma. Methods: A total of 233 children were enrolled in this study. Among them, 116 were asthmatic children and 117 were healthy children. Spirometry, bronchodilator response (BDR) test, methacholine challenge test, and skin prick test were performed. EBT, fractional exhaled nitric oxide (FeNO), blood eosinophils, and total IgE levels were measured. EBT was measured by using X-halo. Results: EBT was significantly higher in the asthma group than in the control group (median [interquartile range], 32.1°C [30.0°C– 33.9°C] vs. 29.7°C [29.0°C–31.3°C], P<0.001). EBT was significantly higher in poorly or partly controlled asthmatic children than wellcontrolled asthmatic children (33.5°C [31.0°C–34.4°C] vs. 30.3°C [29.3°C–32.9°C], P<0.0001). Among total subjects, EBT was significantly higher in the atopic group than in the nonatopic group (32.4°C [30.3°C–34.0°C] vs. 29.8°C [29.0°C–30.3°C], P<0.001). There were neither significant associations between EBT and BDR (r=0.109, P=0.241) nor between EBT and PC20 (provocation concentration causing a 20% fall in FEV1) in total subjects (r=0.127, P=0.316). EBT did not show any association with FeNO (r=0.353, P=0.071). Conclusion: Our study suggests that EBT might play a role as an ancillary marker for allergic airway inflammation and the degree of control in pediatric asthma patients. Additional studies are required to explore the value of EBT in detail. KCI Citation Count: 1